Horizontal Merger under Strategic Tax Policy - Chih-Chen Liu; Arijit Mukherjee; Leonard F.S. Wang (Center for Economic Studies and ifo Institute (CESifo), 2014)
We show that the presence of a strategic tax policy increases the incentive for a horizontal merger compared to the situation with no tax policy. Thus, we point towards a new factor, viz., strategic tax policy, for increasing the incentive for a horizontal merger that has been ignored in the existing literature. In contrast to the usual belief, we also show that a horizontal merger may benefit the consumers and the society.
Keywords: L13; D43; 330; merger; tax policy; social welfare